Sistem Informasi Manajemen Pemesanan Jasa Percetakan Berbasis Web - Nurmalasari Nurmalasari; Sinta Mayanti; Sri Dewi Ayu Safitri; Mohammad Kamal Reza (LPPM Universitas Bina Sarana Informatika, 2021)
CV. Win Copyright Media Pontianak is a company engaged in the service of printing, where the company is in dire need of the existence of a system of information that can help the workers in the process of booking. The existing system on a CV. Win Copyright Media Pontianak is still done simply by using the book tool and Microsoft Excel as recording media. It can allow the occurrence of errors in registration, less akuratnya the reports made, the delay in the search for the required data and open opportunities making it easy to perform data manipulation. For that is the writer trying to make final assignment on printing services booking information system web -based CV. Win Copyright Media Pontianak. Information system is the best solution to solve the existing problems on the CV. Win Copyright Media, as well as Pontianak with a system that is created can facilitate Parties CV. Win Copyright Media Pontianak in managing existing booking transaction data, as well as make it easier for consumers to conduct transactions online printing ordering